The mediating roles of workplace support and ethical work environment in associations between leadership and moral distress: a longitudinal study of Canadian health care workers during the COVID-19 pandemic - Plouffe, Rachel A.; Nazarov, Anthony; Heesters, Ann M.; Dickey, Chandlee C.; Foxcroft, Laura; Hosseiny, Fardous; Le, Tri; Lum, P. Andrea; Nouri, Maede S.; Smith, Patrick; Richardson, J. Don (Frontiers in Psychology, 2023)
The COVID-19 pandemic has resulted in heightened moral distress among health care workers (HCWs) worldwide. Past research has shown that effective leadership may mitigate potential for the development of moral distress. However, no research to-date has considered the mechanisms by which leadership might have an influence on moral distress. We sought to evaluate longitudinally whether Canadian HCWs’ perceptions of workplace support and ethical work environment would mediate associations between leadership and moral distress. A total of 239 French- and English-speaking Canadian HCWs employed during the COVID-19 pandemic were recruited to participate in a longitudinal online survey. Participants completed measures of organizational and supervisory leadership at baseline and follow-up assessments of workplace support, perceptions of an ethical work environment, and moral distress. Associations between both organizational and supervisory leadership and moral distress were fully mediated by workplace supports and perceptions of an ethical work environment. To ensure HCW well-being and quality of care, it is important to ensure that HCWs are provided with adequate workplace supports, including manageable work hours, social support, and recognition for efforts, as well as an ethical workplace environment.